(untitled) (Journal of Statistical Research, 2025)
In this paper, we propose a new class of modified skew-normal distribution as a special case of the modified skew-normal distribution proposed by Kumar and Anusree (2014) is considered. We explore some of its key properties by deriving explicit expressions for its distribution function, characteristic function, and other relevant aspects using special functions and simplified moment expressions. Also, its distributional and structural properties are investigated. Additionally, we address the estimation of parameters for this general class of distributions. Journal of Statistical Research 2025, Vol. 59, No. 1, pp. 31-45